Role of Anaesthesia in Intensive Care Unit Patients: A Multicenter Study in Bangladesh (Community Based Medical Journal, 2026)
Management of critically ill patients in the intensive care unit (ICU) is inherently multidisciplinary. Anaesthesia, with its core principles of physiology, pharmacology, and advanced procedural skills, plays a pivotal role in this setting. A multicenter prospective, cross-sectional study was conducted in six hospitals in Mymensingh region of Bangladesh, from July 2024 to September 2025, to assess the role and impact of anaesthesia in the management of critically ill patients in the ICU. A purposive sample of 297 critically ill patients receiving anaesthesia-led interventions got enrolled in this study. Data was collected on the types of anaesthetic techniques and agents used, their indications, and associated clinical outcomes. Endotracheal intubation (64.3%) was the most frequent anaesthesia-led intervention, followed by central venous access (48.1%). The overall procedural success rate was high (92.3%), though transient hypotension (9.4%) was the most common complication. Seniority and experience of the specialists was significantly associated with success (consultant 98.5% vs. registrar 87.3%, p60 years and the use of propofol were significantly associated with complications (p